1976
DOI: 10.1002/eji.1830061018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sera from immunologically altered mice on phytohemagglutinin‐induced mouse lymphocyte transformation

Abstract: The DNA-synthetic response of mouse spleen cells to phytohemagglutinin in vitro is depressed by the addition of normal mouse serum. The effects of sera from mice that had been modified immunologically were examined. Increased depressive activity was found in sera from nude mice and from mice recently treated with anti-thymocyte globulin, but no change was found in sera from thymectomized, irradiated, bone marrow-reconstituted mice, nor from lethally or sublethally irradiated or cyclophosphamide-treated mice. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…In many human diseases serum from patients either fails adequately t o support, or inhibits, lymphocyte transformation [2-41. For example, normal human lymphocytes respond less well to PHA [3, 51, mitogens [6] or allogeneic lymphocytes [7] in the presence of serum from patients with leprosy than in normal human serum. Uremic serum or plasma actively inhibits the response of normal human lymphocytes t o PHA [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In many human diseases serum from patients either fails adequately t o support, or inhibits, lymphocyte transformation [2-41. For example, normal human lymphocytes respond less well to PHA [3, 51, mitogens [6] or allogeneic lymphocytes [7] in the presence of serum from patients with leprosy than in normal human serum. Uremic serum or plasma actively inhibits the response of normal human lymphocytes t o PHA [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that patients with Virchowian hanseniasis (COCHRANE & SMYLY, 1964;RABELLO JR., 1938;RABELLO JR. & AZULAY, 1975;ROTBERG, 1937) present a deficit of. cell mediated immunity (CMI) (BLADEN, 1974;BULLOCK JR., 1968CONVIT et a/., 1971;GODAL, 1978;MACKANESS & BLADEN, 1967;MILLER & OSOBA, 1967;NELSON, 1974;NELSON et al, 1971;NORTH, 1973;SER. INF.…”
Section: Introductionmentioning
confidence: 99%